Signal transduction and activation of the NADPH oxidase in eosinophils - Mark A Lindsay; Mark A Giembycz (Memorias do Instituto Oswaldo Cruz, 1997)
Activation of the eosinophil NADPH oxidase and the subsequent release of toxic oxygen radicals has been implicated in the mechanism of parasite killing and inflammation. At present, little is known of the signal transduction pathway that govern agonist-induced activation of the respiratory burst and is the subject of this review. In particular, we focus on the ability of leukotrine B4 to activate the NADPH oxidase in guinea-pig peritoneal eosinophils which can be obtained in sufficient number and purity for detailed biochemical experiments to be performed.